Nuevos registros de helmintos parásitos de peces elasmobranquios de las costas del Perú - Tantaleán V., Manuel; Rodríguez, José (Revista de Biología Tropical, 1987)
Four parasites of elasmobranch fishes are recorded for the first time in the peruvian coast. They are: Trematoda: Anaporrhutum albidum Brandes in Ofenheim, 1900. Cestoda: Prochristianella heteracantha Dailey & Carvajal. 1976: Acanthobothroides thorsoni Brooks, 1977 and Nematoda: Proleptus obtusus Dujardin, 1845.